Climate Change and Multifamily Housing: The Influence of Balcony Sill Materials on Thermal Performance of Apartment in Vitória/ES - Borges, Camila Mauro; Pagel , Érica Coelho (Scientific Journal ANAP, 2025)
Objective – To evaluate the thermal performance of different types of materials used in balcony sills in a multifamily apartment in hot and humid climate, considering the context of rising global temperatures.Methodology – Field experiments for model calibration, followed by computer simulations using DesignBuilder software to evaluate current and future thermal performance, comparing translucent (glass) and opaque (masonry) parapets, with analysis of associated energy consumption and financial costs.Originality/Relevance – The study fills a gap in understanding the thermal and energy impacts of balcony enclosures in tropical climates, especially considering future climate projectionsResults – The masonry parapet showed better thermal performance, with a 7.7% increase in comfort hours on the balcony and 4.3% in the adjacent living room. Future projections indicate significant reduction in thermal comfort for both configurations.Theoretical/Methodological Contributions – Development of an integrated methodology combining on-site measurements, computer simulations, and future climate scenario analysis for building thermal performance evaluation.Social and Environmental Contributions – Provides support for reviewing construction regulations and developing more sustainable architectural solutions, aiming at reducing energy consumption and adaptation to climate change
Keywords: Bioclimatic architecture; Thermal performance; Energy efficiency